Studies on conservation and domestication of endangered and threatened medicinal plant species in India - A review - NEGI, MEENAKSHI; TYAGI, KAVITA; RAWAT, M S; ULKHAIR, SHAHID (The Indian Journal of Agricultural Sciences, 2015)
The studies were undertaken under the aegis of the National Medicinal Plants Board (NMPB), New Delhi during 2002 - 2013, comprising in-situ and ex-situ conservation projects implemented through different State Forest Departments. Besides, R&D projects carried out by the ICAR, ICFRE, CSIR, DBT, SAUs have been taken. The contribution of NMPB in conservation and cultivation of endangered and threatened medicinal plant species in India is highlighted. There are several factors which are responsible for endangering these species in their natural habitat such as habitat loss due to diversion of forest land, biotic and abiotic interference in forest areas, unsustainable harvesting of medicinal and aromatic plants. The NMPB has supported several projects for conservation and cultivation of endangered and threatened medicinal plant species, viz.Commiphora wightii (A.) Bhandari,Saraca asoca (Roxb.) de Wilde, Swertia chirayita (Roxb. ex Fleming), Aconitum heterophyllum Wall. ex Royle., Aquilaria malaccensis Lamk., Gloriosasuperba L.Nardostachys grandiflora DC., Picrorhizakurroa Royle ex Benth., Podophyllumhexandrum Royle, Pterocarpus marsupium Roxb., Pterocarpus santalinus L. f., Taxus wallichiana Zucc., Dashmool species etc in different states of the country. The NMPB has funded the establishment of 66 Medicinal Plant Conservation Areas (MPCAs) and 368 herbal gardens in different states. To encourage conservation, domestication and R&D activities, all the stakeholders need to be sensitized as to the cause of loss of species and the ways to address the problem. Make it more informative and attractive.